Suppression of Light-Induced Oxidative Stress in the Retina by Mitochondria-Targeted Antioxidant - Viktoriia E. Baksheeva; Veronika V. Tiulina; Natalia K. Tikhomirova; Olga S. Gancharova; Sergey V. Komarov; Pavel P. Philippov; Andrey A. Zamyatnin; Ivan I. Senin; Evgeni Yu. Zernii (MDPI AG, 2018)
Light-induced oxidation of lipids and proteins provokes retinal injuries and results in progression of degenerative retinal diseases, such as, for instance, iatrogenic photic maculopathies. Having accumulated over years retinal injuries contribute to development of age-related macular degeneration (AMD). Antioxidant treatment is regarded as a promising approach to protecting the retina from light damage and AMD. Here, we examine oxidative processes induced in rabbit retina by excessive light illumination with or without premedication using mitochondria-targeted antioxidant SkQ1 (10-(6’-plastoquinonyl)decyltriphenyl-phosphonium). The retinal extracts obtained from animals euthanized within 1–7 days post exposure were analyzed for H2O2, malondialdehyde (MDA), total antioxidant activity (AOA), and activities of glutathione peroxidase (GPx) and superoxide dismutase (SOD) using colorimetric and luminescence assays. Oxidation of visual arrestin was monitored by immunoblotting. The light exposure induced lipid peroxidation and H2O2 accumulation in the retinal cells. Unexpectedly, it prominently upregulated AOA in retinal extracts although SOD and GPx activities were compromised. These alterations were accompanied by accumulation of disulfide dimers of arrestin revealing oxidative stress in the photoreceptors. Premedication of the eyes with SkQ1 accelerated normalization of H2O2 levels and redox-status of lipids and proteins, contemporarily enhancing AOA and, likely, sustaining normal activity of GPx. Thus, SkQ1 protects the retina from light-induced oxidative stress and could be employed to suppress oxidative damage of proteins and lipids contributing to AMD.